A new numerical technique for solving the local fractional diffusion equation: Two-dimensional extended differential transform approach - Yang, Xiao-Jun (2015)
n this article, we ﬁrst propose a new numerical technique based upon a certain two-dimensional extended differential transform via local fractional derivatives and derive its as-sociated basic theorems and properties. One example of testing the local fractional diffusion equation is then considered. The numerical result presented here illustrates the eﬃciency and accuracy of the proposed computational technique in order to solve the partial differential equations involving local fractional derivatives.